Implementasi Pendidikan Karakter Demokratis Dan Disiplin Dalam Pembelajaran Penjasorkes Pada Siswa Di SD Negeri 1 Kemiri Boyolali - Prasetya, Harry; , Dr. Achmad Fathoni, M.Pd (2017)
This research aims to describe : 1) Implementation of education democratic character and discipline in learning penjasorkes on students at SDN 1 Kemiri Boyolali, 2) What are the support and resistance in the implementation of democratic character education and discipline in learning penjasorkes on students at SDN 1 Kemiri Boyolali, 3) How do solutions to overcome obstacles in the implementation of democratic character education and discipline in learning penjasorkes on students at SDN 1 Kemiri Boyolali. This research is a qualitative research. The informants in this study are the head of the school, PE teachers and students in grade 5 and 6. The data collection techniques use interviews, observation, and documentation. Data analysis techniques through the steps of data reduction, data presentation, and conclusion. Mechanical data validity checking is done by triangulation of sources and techniques. The results shows that in SD N 1 Kemiri has implemented democratic character education and discipline in learning penjasorkes. Supporting the implementation of democratic character education and discipline in learning penjasorkes is committed to character education teacher while obstacles when planning learning difficulties to enter the character values in accordance with the learning materials that emphasize psychomotor aspects. Solutions provided by talking through KKG in the manufacture of lesson plan to include the character values corresponding learning material.